2023
DOI: 10.3390/su15065272
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Stress in Children and Adolescents during the COVID-19 Pandemic: A Meta-Analysis and Intervention Approaches to Ensure Mental Health and Well-Being

Abstract: Background: Since the World Health Organization (WHO) declared the COVID-19 pandemic in March 2020, many measures have been taken to prevent the spread of the virus. Consequently, many minors have been confined to their homes and have had to subsequently adapt to countless protocol changes. These factors appear to have contributed to post-traumatic stress disorder (PTSD) in many children. Materials and Methods: The authors searched Medline through PubMed and other databases for studies published from 1 Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Experiences from previous epidemics have shown that 42% of MERS survivors and 26% of SARS survivors presented PTSD symptoms following the outbreak [ 10 , 11 ]. Similarly, extensive body of evidence from systematic reviews and metaanalyses reported high prevalence estimates of COVID-19-related PTSD in various populations worldwide, including the adult general population [ 12 ],children and adolescents [ 13 ] university students [ 14 , 15 ], teachers [ 16 ], healthcare workers [ 17 , 18 ], survivors of COVID-19 infection [ 19 ], and in high risk groups (e.g., older adults, pregnant women, obese individuals, smokers, individuals with obesity or other comorbidities ) [ 20 ]. Arab people are of no exception (e.g., [ 21 24 ], even though evidence on the topic from this population remains relatively scant.…”
Section: Introductionmentioning
confidence: 99%
“…Experiences from previous epidemics have shown that 42% of MERS survivors and 26% of SARS survivors presented PTSD symptoms following the outbreak [ 10 , 11 ]. Similarly, extensive body of evidence from systematic reviews and metaanalyses reported high prevalence estimates of COVID-19-related PTSD in various populations worldwide, including the adult general population [ 12 ],children and adolescents [ 13 ] university students [ 14 , 15 ], teachers [ 16 ], healthcare workers [ 17 , 18 ], survivors of COVID-19 infection [ 19 ], and in high risk groups (e.g., older adults, pregnant women, obese individuals, smokers, individuals with obesity or other comorbidities ) [ 20 ]. Arab people are of no exception (e.g., [ 21 24 ], even though evidence on the topic from this population remains relatively scant.…”
Section: Introductionmentioning
confidence: 99%